Percepciones de la inclusión escolar en estudiantes de educación secundaria (2012)
ABSTRACT: The research project “Perceptions of school inclusion in students from the Institución Normal Educativa de Envigado, (Normal Superior Education Institute of Envigado) Antioquia”, carried out as graduation project at the Institución Universitaria de Envigado (University Institution of Envigado) in 2010, studies the perception high school students of the Envigado educational institute have on the cultural, politic and practical aspects of inclusion strategies. This was done through a questionnaire with Likert type answers that is proposed in the Index for Inclusion guide, created to develop learning and participation in schools. We employed a quantitative research focus with a simple descriptive design. We surveyed 185 students from the institution aged between 12 and 18 years. The study found that in this institution the perception the students have on the mentioned aspects of this policy tends towards the mean. However, women have a lower perception of inclusive practices than men. Moreover, we found that students from the intermediate ages of the sample have a worse perception of inclusion at a cultural and practical level, when compared to the perception of subjects with ages towards the extremes of the studied group.